Development and characterization of conductive graphene-coated prepreg composites for aviation application - Alemour, Belal Jamal Tawfiq (2020)
Developing a conductive composite using graphene is very important in manufacturing aircraft’s structures toward enhancing their electrical and thermal properties for future aviation application. Consequently, this study was conducted to develop a method to coat carbon fiber reinforced epoxy composite (CFRE) with reduced graphene oxide (rGO) and functionalized graphene nanoplates (FGNP) to improve and enhance the electrical conductivity and self- heating properties of CFRE in order to obtain an outstanding conductive composite . Hence, this study started with identifying the gab in evaluating the available carbon fiber reinforced epoxy composite, then painting method was used in this study to coat CFRE with rGO, while inkjet printing method was used to coat CFRE with FGNP, after that the conductive composites (CFRE/rGO and CFRE/FGNP) was fabricated using hot press molding method, then many experiments were conducted on conductive composites to evaluate it’s electrical and thermal properties. Firstly, atomic force microscopy, morphological characterization and tensile tests were conducted to evaluate the quality of conductive composites. Secondly, four point probe device was used to measure the electrical conductivity value for conductive composites. Finally, experimental work were conducted to study the self-heating of conductive composites.